(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Derivatives market has an important role play in the economic development of a country. The Objective of the study is derivative market problems and prospects. The retail and Intuitional Investors occupied a key role in development of derivatives trading in India. Retail Investors are the major participants in equity derivatives have contributed 54% higher when comparing with Intuitional investment; this study has been taken to identify the retail investor’s perception on derivatives trading. The research design chosen is descriptive. The data was used collected using a questionnaire that consists of close ended questions. Convenient sampling method is employed in Visakhapatnam District. After review the available literature the statically Analysis were performed by using % Analysis, Chi-Square Test and; F-Test.